Verbal Deception and the Model Statement as a Lie Detection Tool - Vrij, Aldert; Leal, Sharon; Fisher, Ronald P. (Frontiers in Psychiatry, 2018)
We have been reliably informed by practitioners that police officers and intelligence officers across the world have started to use the Model Statement lie detection technique. In this article we introduce this technique. We describe why it works, report the empirical evidence that it works, and outline how to use it. Research examining the Model Statement only started recently and more research is required. We give suggestions for future research with the technique. The Model Statement technique is one of many recently developed verbal lie detection methods. We start this article with a short overview of the –in our view- most promising recent developments in verbal lie detection before turning our attention to the Model Statement technique.